Robust fuzzy tracking control of a quad-rotor unmanned aerial vehicle based on sector linearization and interval matrix approaches. (September 2018) - Sun, Miaoping; Liu, Jingjing; Wang, Haibo; Nian, Xiaohong; Xiong, Hongyun
Abstract: In this paper, the robust H ∞ fuzzy tracking control strategy for a quad-rotor unmanned aerial vehicle (UAV) with strong coupling and highly nonlinear is put forward based on the Takagi-Sugeno(T-S) fuzzy error model. Firstly, the quad-rotor UAV system is divided into altitude subsystem, position subsystem and attitude subsystem. Through selecting appropriate premise variables, three T-S fuzzy error models, which are equivalent to the error dynamic model, are established by the sector linearization approach. Next, the uncertainties in drag coefficients, moments of inertia are taken into account, and the interval matrix is introduced to describe them in altitude, position and attitude T-S fuzzy error models. Then the robust H ∞ fuzzy feedback controllers are designed to stabilize T-S fuzzy subsystems. Besides, according to the Lyapunov stability theorem, it is obtained that the LMI sufficient conditions of exponential stability with the prescribed H ∞ performance for T-S fuzzy closed-loop subsystems. Meanwhile, the method for solving the gain matrices of controller is presented. Finally, simulation results are given to demonstrate the effectiveness, robustness and advantages of the proposed method. Then the feasibility of the proposed method is further verified by experimental results. Highlights: The equivalent T-S fuzzy error models are established based on sector linearization approach. The interval matrix is introduced to describe the parameters changing within a certain range. The LMI exponential stability sufficient conditions with the prescribed H ∞ performance are derived. Simulations are done to demonstrate the robustness, effectiveness and advantages. Experiment is conducted to further validate the feasibility.